Comparative reliability of screening parameters for anthracnose resistance in water yam (Dioscorea alata) - Nwadili, C.O.; Augusto, J.; Bhattacharjee, Ranjana; Atehnkeng, J.; López Montes, Antonio José; Onyeka, T.J.; Kumar, P. Lava; Asiedu, Robert; Bandyopadhyay, Ranajit (Scientific Societies, 2017)
Anthracnose, caused by Colletotrichum gloeosporioides, is one of the major constraints limiting water yam (Dioscorea alata) production in the tropics. In this region, yam anthracnose control is mostly achieved by the deployment of moderately resistant yam genotypes. Therefore, screening for new sources of anthracnose resistance is an important aspect of yam research in the tropics. The reliability and applicability of different yam anthracnose rating parameters has not been fully examined. Disease severity on detached leaves in the laboratory and leaf severity, lesion size, and spore production on whole plants in the greenhouse were used to screen an F1 yam population and correlate screening results with field evaluations. Anthracnose lesion size had the smallest predicted residual means but whole-plant severity and detached-leaf severity had the best variance homogeneity and relatively small predicted residual means. The concordance correlation coefficient (rc) and κ statistic were used to determine the agreement between anthracnose rating parameters and field evaluations. Detached-leaf (rc = 0.95, κ = 0.81) and whole-plant (rc = 0.96, κ = 0.86) evaluations had high positive agreement with field evaluation but spore production (κ = 0.69) and lesion size (κ = 0.57) had moderate positive agreement. These results suggest that all the evaluated rating parameters can be used to successfully screen yam germplasm for anthracnose resistance but lesion size and spore production data may need to be transformed.